2009
DOI: 10.1016/j.acap.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Update on Early Childhood Caries Since the Surgeon General's Report

Abstract: The 2000 Surgeon General's Report on Oral Health (SGROH) included a limited discussion of the condition known as Early Childhood Caries (ECC). Because of its high prevalence, its impact on young children's quality of life and potential for increasing their risk of caries in the permanent dentition, ECC is arguably one of the most serious and costly health conditions among young children. A necessary first step in preventing dental caries in preschool children is understanding and evaluating the child's caries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
164
0
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 53 publications
0
164
0
16
Order By: Relevance
“…However, in this low socioeconomic sample, the mothers from the wealthier tertile had a decreased likelihood of presenting offspring with a high level of caries. Children from low socioeconomic status are likely to have more ECC at the preschool age (24). The similarity of low socioeconomic status in this sample of adolescent mothers may be considered a limitation of this study, since it could impair the observation of potential associations.…”
Section: Discussionmentioning
confidence: 87%
“…However, in this low socioeconomic sample, the mothers from the wealthier tertile had a decreased likelihood of presenting offspring with a high level of caries. Children from low socioeconomic status are likely to have more ECC at the preschool age (24). The similarity of low socioeconomic status in this sample of adolescent mothers may be considered a limitation of this study, since it could impair the observation of potential associations.…”
Section: Discussionmentioning
confidence: 87%
“…Several epidemiological population-based studies have demonstrated a significant decrease in caries worldwide, a fact that is not demonstrated when the object of the study are preschool children (3). Well-designed epidemiological studies provide a picture of the population and are important tools in defining the distribution of funds for oral health programs and the implementation of preventive policies by stakeholders (4).…”
Section: Introdutionmentioning
confidence: 99%
“…14,15 It is a disease of the calcified tissues of the teeth caused by the action of microorganisms on fermentable carbohydrates. Sugars are known to be the principal etiologic agent for dental caries.…”
Section: Discussionmentioning
confidence: 99%